Higher education, stakeholders and collaborative work for entrepreneurial learning - Marques, Ana Paula (2014)
Institutions of Higher Education can provide, in their internal environment, entrepreneurial learning opportunities for students stimulating new attitudes and behaviours towards entrepreneurship. The Portuguese universities have diversified their strategies to promote formal, informal and non formal entrepreneurial learning that can be encouraged in various strategies. The participation of key actors and stakeholders involved in awareness,mentoring and project implementation of the entrepreneurial learning process is crucial for collaborating work in a competitive world. Moreover, obtaining employment is increasingly dependent on not only the potentials of individuals, but also, and even more, the ability to build solid networks of partnerships in science and innovation and employment. Within the scope of the ongoing project "Entrepreneurial Learning, Cooperation and the Labour Market: Good Practice in Higher Education" this paper aims to highlight the importance of non formal and informal learning and to contribute to the reflection regarding added value of inter organizational cooperation and collaborative work.